(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This thesis analyzes the pressing issues in medical psychology, neurology, and psychiatry through innovative approaches. The research explores the possibilities of applying new technologies and methods in the diagnosis, treatment, and rehabilitation of psychological and neurological disorders. Furthermore, the paper discusses the effectiveness of modern psychiatric practices and innovative solutions in working with patients.